Pengaruh Kualitas Pelayanan Check-In Counter Terhadap Kepuasan Pelanggan Maskapai Wings Air di Bandar Udara Rahadi Oesman - Yudistira Pamungkas; Andityo Pujo Laksana (Student Scientific Creativity Journal, 2023)
The quality of service provided at the Check-in counter is an important factor that affects passenger satisfaction to choose an airline. The quality of service at the Check-in counter includes speed of service, friendliness of officers, availability of necessary information, clarity of procedures, and quality of facilities and equipment provided. The quality of service at the Check-in counter can affect the image and reputation of the airline in the eyes of the public. If the quality of service at the Check-in counter is poor, passengers tend to give negative reviews and potentially damage the image of the airline. This study aims to determine whether there is an influence and how much influence the quality of Check-in counter service on customer satisfaction of Wings Air at Rahadi Oesman Ketapang airport. This study used quantitative methods, with sampling techniques in this study using Purposive Sampling techniques. The data collection technique uses a questionnaire with measurements using the Likert scale. The results of the study show that the quality of Check-in counter service affects passenger satisfaction. This can be proven by the results of significant values of 0.00 < 0.05 and T Test 13,596 > 1.661. The value of the Coefficient of Determination (R2) is 0.654 This means that the relationship between the independent variable and the dependent variable is 65.4%..